THE USE OF M-U-F FRAMEWORK IN IMPROVING SPEAKING ABILITY OF YOUNG LEARNERS - Hermyati, Indah (2014)
ABSTRACT This research was purposed to investigate whether there is any improvement of students' speaking skill by the implementation of M-U-F framework and discover students' response to the use of M-U-F framework in teaching speaking to young learner. This research employed quantitative method. This quantitative research involved two classes of fourth grade at elementary school in Tasikmalaya in which one class was assigned as the experimental group and the other one was the control group. The instruments used were pretest, posttest, and questionnaire. The posttest scores of the two groups were compared by using Independent t-test. The results showed the significance value was lower than the significance level which was 0.000 < 0.05. It meant that M-U-F framework improved students' speaking skill. Keywords: M-U-F framework, young learner, EFL, speaking skill ABSTRAK Penelitian ini bertujuan untuk menginvestigasi apakah ada peningkatan dari kemampuan berbicara siswa dengan menggunakan M-U-F framework dan menelaah respon dari siswa tentang penggunaan M-U-F framework dalam pembelajaran berbicara pada siswa kanak-kanak. Penelitian ini dilakukan dengan menggunakan metode kuantitatif. Penelitian kuantitatif ini menyediakan dua kelas dari kelas 4 sekolah dasar di Tasikmalaya yang mana satu kelas sebagai kelas eksperimental dan yang satunya lagi kelas kontrol. Instrumen penelitian yang digunakan yaitu pretest, posttest, dan kuesioner. Nilai posttest dari kedua kelas dihitung menggunakan perhitungan Independent t-test. Hasil perhitungan menunjukan bahwa nilai signifikansinya lebih rendah dari level signifikansinya yaitu 0.000 < 0.05. itu berarti bahwa M-U-F framework telah meningkatkan kemampuan berbicara siswa.